2013
DOI: 10.1002/jnr.23307
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein attenuates astroglial activation in the 1‐methyl‐4‐phenyl‐1,2,3,4‐tetrahydropyridine‐induced Parkinson's disease model by downregulating the activations of nuclear factor‐κB, ERK, and JNK

Abstract: In Parkinson's disease (PD), neuroinflammation plays a critical role in the neurodegenerative process. Furthermore, activated microglia and astrocytes, responsible for activated immune response in the central nervous system, are found in regions associated with dopaminergic neuronal death. The flavonoid baicalein is known to have antibacterial, antiviral, and antiinflammatory activities. In the present study, the neuroprotective effects of baicalein were examined in a murine 1-methyl-4-phenyl-1,2,3,4-tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(49 citation statements)
references
References 54 publications
5
42
0
2
Order By: Relevance
“…Post-mortem analysis and in vivo imaging of PD patient brains showed activation of microglia, astrogliosis and infiltration of peripheral immune cells in the SN and STR (Hirsch et al, 1998; Ouchi et al, 2009; Tansey and Goldberg, 2010). These features were also observed in experimental rodents brain after MPTP treatment (Khan et al, 2013; Lee et al, 2014; Noelker et al, 2013). The glia maturation factor (GMF), discovered and characterized in our laboratory, is a conserved protein in mammalian brain/central nervous system (Lim et al, 1989; Lim et al, 1990; Zaheer et al, 2011a).…”
Section: Introductionsupporting
confidence: 52%
“…Post-mortem analysis and in vivo imaging of PD patient brains showed activation of microglia, astrogliosis and infiltration of peripheral immune cells in the SN and STR (Hirsch et al, 1998; Ouchi et al, 2009; Tansey and Goldberg, 2010). These features were also observed in experimental rodents brain after MPTP treatment (Khan et al, 2013; Lee et al, 2014; Noelker et al, 2013). The glia maturation factor (GMF), discovered and characterized in our laboratory, is a conserved protein in mammalian brain/central nervous system (Lim et al, 1989; Lim et al, 1990; Zaheer et al, 2011a).…”
Section: Introductionsupporting
confidence: 52%
“…The current study investigated the mechanism underlying these effects by inducing a PD-like syndrome using rotenone, as evidenced by the diminished performance on the rotarod test and loss of dopaminergic neurons in the midbrain (Fig. 1), which was consistent with results of previous studies that used 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine to induce PD (Costa et al, 2013;Toy et al, 2013;Lee et al, 2014). An assessment of gait using catwalk analysis revealed that rotenone caused a shortening of print width and length, which is consistent with published reports of 6-OHDAinduced PD (Chuang et al, 2010), (Hsieh et al, 2011) and comparable to what is observed in PD patients who experience rigidity of the muscles that consequently limits movement.…”
Section: Discussionsupporting
confidence: 81%
“…Enhanced inflammatory response and oxidative stress caused by microglia activation may play a crucial role in PD by mediating dopaminergic cell death [30,48,49]. Transduced PEP-1-PON1 proteins inhibited MPP þ induced oxidative stress in SH-SY5Y cells which can lead to mitochondria dysfunction and intrinsic apoptotic signaling.…”
Section: Discussionmentioning
confidence: 98%